2014
DOI: 10.1541/ieejjia.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Thermo-Mechanical Analysis of High-Power Press-Pack Insulated Gate Bipolar Transistors under Various Mechanical Clamping Conditions

Abstract: With the continuously increasing demand for energy and the limited supply of fossil fuels, renewable power sources are becoming ever more important. Knowing that future energy demand will grow, manufacturers are increasing the size of new wind turbines (WTs) in order to reduce the cost of energy production. The reliability of the components has a large impact on the overall cost of a WT, and press-pack (PP) insulated gate bipolar transistors (IGBTs) could be a good solution for future multi-megawatt WTs becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The heat flow generated from a Peltier device includes heat from a Peltier effect, a Joule heat, and heat interference inside the device. The thermal system is modeled based on a thermal network method (28) (29) that a thermal behavior is expressed as a electric circuit. In this paper, the heat flow generated from a Peltier device is expressed as…”
Section: Definition Of Disturbance Heat Flowmentioning
confidence: 99%
“…The heat flow generated from a Peltier device includes heat from a Peltier effect, a Joule heat, and heat interference inside the device. The thermal system is modeled based on a thermal network method (28) (29) that a thermal behavior is expressed as a electric circuit. In this paper, the heat flow generated from a Peltier device is expressed as…”
Section: Definition Of Disturbance Heat Flowmentioning
confidence: 99%
“…Finite element analysis (FEA) as a modelling and analysis tool of press packs has been undertaken by many researchers. A FEA study on press pack insulated bipolar transistor (PPIGBT) was presented by Busca et al [4] for the impact of mechanical clamping pressure on the thermal distribution among the chips. Another thermo mechanical FEA study on PPIGBT was reported by Poller et al [5 and 6] who investigated the effect of external clamping pressure on the thermo mechanical behavior of an IGBT chip.…”
Section: Fig 2: Press Pack Single Diode Devicementioning
confidence: 99%
“…Since PP IGBTs abandon wire bonding connections, both electrical connections and thermal dissipation use a press pack, and the connection state of each chip is linked to the current path and cooling capacity [6]. The failure test developed by Poller shows that micro-electrical discharge is a possible failure mode and is caused by lost contact between metal layers [7].…”
Section: Introductionmentioning
confidence: 99%
“…As the clamping force increases, the on-state voltage and contact resistance of the PP IGBTs decreases [22]. In addition, the stress distribution is affected by the geometric structure of the fixture [6]. The clamping fixture with a cylindrical shape is a better choice for maintaining the internal stress and temperature distribution.…”
Section: Introductionmentioning
confidence: 99%